TLR-dependent T cell activation in autoimmunity. - MILLS, KINGSTON (My University, 2011)
Autoimmune disease can develop as a result of a breakdown in immunological tolerance, leading to the activation of self-reactive T cells. There is an established link between infection and human autoimmune diseases. Furthermore, experimental autoimmune diseases can be induced by immunization with autoantigens that are administered together with complete Freund?s adjuvant containing killed Mycobacteria tuberculosis, which in some cases can be replaced with individual pathogen-associated molecular patterns (PAMPs). Exogenous PAMPs and endogenous danger signals from necrotic cells bind to pathogen recognition receptors, including Toll-like receptors, and activate signaling pathways in innate immune cells and on T cells, leading to inflammatory cytokine production and T cell activation, and this is now considered to be a major factor in the development of autoimmunity.
PUBLISHED
Keywords: autoimmunity; TLR; T cells; infection; PAMPs; DAMPS; Immunology, Inflammation & Infection